Flood forecasting a global perspective - Adams, Thomas E.,III; Pagano, Thomas C. (Amsterdam Academic Press, 2016)
Flood Forecasting: A Global Perspective describes flood forecast systems and operations as they currently exist at national and regional centers around the globe, focusing on the technical aspects of flood forecast systems. This book includes the details of data flow, what data is used, quality control, the hydrologic and hydraulic models used, and the unique problems of each country or system, such as glacial dam failures, ice jams, sparse data, and ephemeral streams and rivers. Each chapter describes the system, including details about its strengths and weaknesses, and covers lessons learned. This helpful resource facilitates sharing knowledge that will lead to improvements of existing systems and provides a valuable reference to those wishing to develop new forecast systems by drawing on best practices.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Flood forecasting; Electronic books